Produksi Etanol Dari Limbah Kulit Nanas Dengan Metode Solid State Fermentation (SSF) Terhadap Variasi Waktu Dan Variasi Ukuran Partikel Substrat - Reni Oktaviani; Chairul Chairul; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Solid State Fermentation (SSF) is a form of solid substrate fermentation with low humidity levels. This study aims to determine the maximum time of the fermentation process to produce ethanol with SSF method and studying the kinetics of cell growth of Zymomonas mobilis for variations in particle size of the substrate. Pineapple peel waste is used as a raw material with a variety particle size of substrate in the form of slurry, 1x1 cm and 2x2 cm. Time of fermentation sampling conducted in 6; 12; 18; 24, 30, and 36 hours. Environmental conditions Zymomonas mobilis growth adjusted to pH 5 and 30 ° C. Analysis carried out in the study is the analysis of ethanol content using alcoholmeter and calculation of the number of cells by turbidity method using UV spectrophotometer to determine the kinetics of cell growth of Zymomonas mobilis. The maximum time obtained in this study was 24 hours for all particle size of the substrate. In  fermentation process with the SSF method, the kinetics of cell growth of Zymomonas mobilis and ethanol concentration is influenced by the particle size of the substrate. The highest ethanol concentrations obtained was 33% V on substrate particle size slurry with maximum specific growth rate  0,43/hour Keyword : Fermentation, Solid State Fermentaton (SSF), Zymomonas mobilis, Pineapple peel, kinetics cell, ethanol